A Short Note on ‘Responsibility’ and ‘Engagement’ - Khairil Annuar, Mohd Kamal (Social Science Research Network, 2016)
In this paper I illustrate my simple thoughts on what I argue to be empty and vague concepts of 'responsibility' and 'engagement'. I argue that 'responsibility' and 'engagement' are aspirations of the hegemonic stakeholders that are imposed to the subaltern stakeholders. In other words the concepts of 'responsibility' and 'engagement' are nothing but tools for hegemonic stakeholders to exert power over the subaltern stakeholders.